Analisis manajemen logistik farmasi di Rumah Sakit Jiwa Grhasia Yogyakarta - Wahyu Listiana; Rochana Ruliyandari (International Journal of Healthcare Research, 2020)
Hospital Pharmacy Installation (IFRS) is a hospital unit as a place to carry out drug management activies. Pharmaceutical logistics management is the process of managing hospital pharmaceutical preparations ranging from planning, budgeting, procurement, storage, distribution, recording and reporting well as drug destruction in accordance with standard operating procedures. In the pharmacy installation of Yogyakarta Grhasia Mental Hospital have experienced drug vacancies in pharmaceutical logistics warehouses caused by empty stock of medicines from factories and the e- catalog process which is hampered in the procurement function the delivery or invoice inadequacy. This study aims to determine the management of pharmaceutical logistics in the Grhasia Yogyakarta Mental Hospital pharmaceutical installation. This type of research is descriptive qualitative, with a phenomenological approach. The sampling technique used is Purposive Sampling. The number of informants in this study were 5 informants consisting of the Head of the Pharmacy Installation Section, the Head of the Medical Support Services Division, the Logistics Warehouse Coordinator, and the Pharmacist as the Coordinator of drug abolition. This study uses interview guidelines and observation checklist instruments. Pharmaceutical logistics management in Yogyakarta Grhasia Mental Hospital in the implementation of the management functions of procurement, storage, distribution, recording and reporting have not run optimally in accordance with standard operating procedures. Lack of human resources and inadequate facilities become obstacles in the implementation of pharmaceutical logistics management. Pharmaceutical logistics management in pharmaceutical installation of Yogyakarta Mental Hospital Grhasia has not run optimally in accordance with standard operating procedures. The need for evaluation related to human resources and the availability of existing facilities in hospital pharmaceutical installations.